Phage Therapy: Towards a Successful Clinical Trial - Górski, Andrzej (Antibiotics (Basel), 2020)
While phage therapy carried out as compassionate use (experimental therapy) has recently flourished, providing numerous case reports of supposedly healed patients, clinical trials aiming to formally prove their value in accord with current regulatory requirements have failed. In light of the current issue of increasing antibiotic resistance, the need for a final say regarding the place of phage therapy in modern medicine is evident. We analyze the possible factors that may favor success or lead to the failure of phage therapy: quality of phage preparations, their titer and dosage, as well as external factors that could also contribute to the outcome of phage therapy. Hopefully, better control of these factors may eventually bring about long-awaited positive results.